Neuropathic Pain Induced Alterations in the Opioidergic Modulation of a Descending Pain Facilitatory Area of the Brain - Costa, Ana Rita; Carvalho, Paulina; Flik, Gunnar; Wilson, Steven P.; Reguenga, Carlos; Martins, Isabel; Tavares, Isaura (Frontiers in Cellular Neuroscience, 2019)
Opioids play a major role at descending pain modulation but the effects of neuropathic pain on the brain opioidergic system remain understudied. Since descending facilitation is enhanced during neuropathic pain, we studied the opioidergic modulation of the dorsal reticular nucleus (DRt), a medullary pain facilitatory area, in the spared nerve injury (SNI) model of neuropathic pain. We first performed a series of behavioral experiments in naïve-animals to establish the role of MOR in the effects of endogenous and exogenous opioids at the DRt. Specifically, we showed that lentiviral-mediated MOR-knockdown at the DRt increased sensitivity to thermal and mechanical stimuli while the MOR agonist DAMGO induced the opposite effects. Additionally, we showed that MOR-knock down and the pharmacological blockade of MOR by CATP at the DRt decreased and inhibited, respectively, the analgesic effects of systemic morphine. Then, we performed in vivo microdialysis to measure enkephalin peptides in the DRt and evaluated mu-opioid receptor (MOR) expression in the DRt at mRNA, protein and phosphorylated form levels by quantitative real-time PCR and immunohistochemistry, respectively. SNI-animals, compared to sham control, showed higher levels of enkephalin peptides, lower MOR-labelled cells without alterations in MOR mRNA levels, and higher phosphorylated MOR-labeled cells. Finally, we performed behavioral studies in SNI animals to determine the potency of systemic morphine and the effects of the pharmacologic and genetic manipulation of MOR at the DRt. We showed a reduced potency of the antiallodynic effects of systemic morphine in SNI-animals compared to the antinociceptive effects in sham animals. Increasing MOR-cells at the DRt of SNI-animals by lentiviral-mediated MOR-overexpression produced no effects on mechanical allodynia. DAMGO induced antiallodynia only after MOR-overexpression. These results show that MOR inhibits DRt pain facilitatory actions and that this action contributes to the analgesic effects of systemic opioids. We further show that the inhibitory function of MOR is impaired during neuropathic pain. This is likely due to desensitization and degradation of MOR which are adaptations of the receptor that can be triggered by MOR phosphorylation. Skipping counter-regulatory pathways involved in MOR adaptations might restore the opioidergic inhibition at pain facilitatory areas.